2014
DOI: 10.1515/ijnes-2013-0061
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth: Preparing Advanced Practice Nurses to Address Healthcare Needs in Rural and Underserved Populations

Abstract: AbstractHealthcare is being confronted with questions on how to deliver quality, affordable, and timely care to patients, especially those in rural areas, in systems already burdened by the lack of providers. Advanced Practice Registered Nurses (APRNs) have been challenged to lead this movement in providing care to these populations through the use of technologies, specifically telehealth. Unfortunately, APRNs have limited exposure to telehealth during their educational experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
92
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 11 publications
2
92
0
Order By: Relevance
“…Trainees were pleased to find that it was possible to provide satisfac-tory care and support at a distance from the patient. Reierson, Solli and Bjørk [2] as well as Rutledge and colleagues [12] have noted similar findings regarding positive perceptions of the value of telecare after participation in simulation-based training. Furthermore, based on their experiences with the simulations, trainees argued that virtual visits had the potential to improve the quality of current services for home healthcare patients.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Trainees were pleased to find that it was possible to provide satisfac-tory care and support at a distance from the patient. Reierson, Solli and Bjørk [2] as well as Rutledge and colleagues [12] have noted similar findings regarding positive perceptions of the value of telecare after participation in simulation-based training. Furthermore, based on their experiences with the simulations, trainees argued that virtual visits had the potential to improve the quality of current services for home healthcare patients.…”
Section: Discussionmentioning
confidence: 57%
“…This is somewhat opposite of previous research findings, where telecare students reported feeling as close to the patient during the simulated telecare encounter as they did during a traditional face-to-face encounter. [12] One explanation for this discrepancy in findings could be the topics of the scenarios enacted and the care tasks concerned within each respective scenario case. In future, simulation-based telecare training initiatives should implement a more diverse range of scenario cases to enable assessment of whether and how particular simulation scenarios may influence trainees' impressions of the telecare experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly critical when working in rural or remote areas (Rutledge et al, 2014). One major obstacle to this however is the availability of broadband in the country.…”
mentioning
confidence: 99%